Application of The 5C Principle in Providing Financing to BNI Syariah Tomoni - Nur Annisah (Journal Of Institution And Sharia Finance, 2021)
This study aims: to find out how to apply the 5C principles in providing financing, as well as to find out the various obstacles that will be faced in implementing the 5C principles in providing financing at BNI Syariah Tomoni. The type of research used is qualitative research. By taking the research location at BNI Syariah Tomoni and the research informants were BNI Syariah Tomoni employees, totaling six people consisting of micro sales heads, micro financing risk officers, micro sales assistants, consumer sales, and processing & collaction assists. Data and data source used, namely primary data. The data collection technique in this study used interview techniques. The results showed that the application of the 5C principles in providing financing to BNI Syariah Tomoni has a very important role because the application of the 5C principles is sought so that banks avoid problem financing. The implementation of the 5C principle is the basis for the leadership of BNI Syariah Tomoni to determine whether the submission of a financing application is approved or rejected. from the ability of the prospective debtor that is not proportional to the nominal amount of the financing submitted to BNI Syariah Tomoni, as well as other obstacles such as the prospective debtor does not have collateral that can be guaranteed.